Entrepreneurial Capacity vs. Education and Self-Efficacy in Gen-Z High-Growth Intentions - Tanesia, Cindy Yoel; Mustikarini, Carolina Novi; Wijaya, Justin (Universitas Ciputra Surabaya, 2024)
This study aims to investigate whether factors such as entrepreneurial capacity, education, and self-efficacy can predict high-growth entrepreneurial intention. The research employs a quantitative method. Data was collected from 300 Gen-Z respondents who had studied entrepreneurship at universities and was analyzed using Structural Equation Modeling with AMOS. The findings reveal that entrepreneurial education does not significantly influence the intention to create a high-growth business. However, both entrepreneurial self-efficacy and capacity significantly and positively affect high-growth entrepreneurial intention.